Diphenhydramine Use in End-Stage Kidney Disease. (March 2021) - Nguyen, Timothy; Polyakova, Beatrice; Cerenzio, John; Ramilo, Josh Renzo
Abstract : Background: Diphenhydramine is commonly used in patients with kidney disease and end-stage kidney disease (ESKD) for sleep, allergic reactions, itching, and dialysis treatment related complications, and misuse associated with diphenhydramine is also reported. Diphenhydramine's pharmacokinetics property is reviewed and discussed. Areas of Uncertainty: Diphenhydramine is highly bound to albumin. The safety profile and dosing information of diphenhydramine use in ESKD population is lacking. The purpose of this study is to provide an overview of diphenhydramine pharmacokinetic properties and evaluate diphenhydramine use in ESKD population. Data Sources: A literature search was conducted during Spring 2019 using PubMed, CINAHL, Cochrane, Ovid, and Google Scholar. Search terms used include "diphenhydramine abuse, " "diphenhydramine dialysis, " and "diphenhydramine kidney disease." Results: There is lack of studies available for diphenhydramine, kidney disease, and dialysis. There were case reports of diphenhydramine abuse and toxicity due to overdose. Diphenhydramine is highly bound to protein that limits its ability to dialyze, and therefore, it may predispose to side effects. Information on diphenhydramine used in the dialysis population is scarce, and dosing toxicity is unknown. Conclusions: The data available for use of diphenhydramine in ESKD and dialysis are limited. Clinicians should use caution with the use of diphenhydramine in this population.